Contemporary perspectives on research on child care in early childhood education - Saracho, Olivia N. (Contemporary perspectives in early childhood education., 2021)
"Child care environments have received extensive research attention by those interested in understanding how participating in nonparental child care might influence the children's development and learning. Throughout the United States (US Census Bureau, 2011) and Europe (Organization for Economic Co-operation and Development, 2006) a large number of young children are cared for outside of the home by non-parental adults. Young children's nonparental care is commonly referred to as "child care," and is provided to children whose ages range from birth to 12 years of age. The provision of child care services has become an increasingly important part of early childhood education. Child care arrangements include center care, family child care, in-home child care, relative child care, and supplemental child care. Child care researchers have been conducting studies to understand how participating in nonparental child care might influence the children's development and learning outcomes. There are more than enough child care studies to make numerous major inferences. For example, research outcomes show that child care quality seems to be more influential than either the kind of child care or age of admission in determining the children's development and learning . The adults' child care affects the quality in child care. In the environment adults who are caring for the children have the opportunity to effectively assume both nurturing and instructional roles to help young children cultivate their social and cognitive abilities. The teachers' effectiveness is related to their individual characteristics, such as formal education, specialized training, and the classroom environment. However, the majority of the studies show that both family and quality of child care have the most significant effects on the children's development and learning. Therefore, the concept of child care has heavily influenced modern views. Researchers, scholars, and educators are beginning to understand the current foundations based on theoretical frameworks that contribute to the purposes of the child care in the United States and Europe. The contents of the child care volume reflect the major shifts in the views of these early childhood researchers, scholars, and educators in relation to research outcomes on child care, its historical roots, the role of child care in early childhood education, and its relationship to theory, research, and practice"--